Working with qualitative data - Gibson, William J.; Brown, Andrew (SAGE Publications, 2009)
Qualitative Data Analysis provides a practical and accessible introduction to data analysis which sees analysis as an integrated part of the whole research process, rather than something to be done after data collection is complete. This sets it apart from other data analysis books.